Strategi Pembelajaran Pendidikan Islam Berbasis Teknologi untuk Generasi Milenial - Syauqi, Muhammad; Wahidin, Ikhwan (LaKaspia, 2025)
The development of digital technology has driven significant transformation in the world of education, including Islamic education. The millennial generation, born and raised amid technological advances, demands adaptive, interactive, and relevant learning methods that align with the digital world they know. This study aims to examine effective technology-based Islamic education learning strategies that address the needs of this generation. The research method used is library research with a descriptive-analytical approach to various related literature. The analysis results indicate that the integration of digital technology such as e-learning, social media, mobile-based learning applications, and interactive platforms can enhance students' motivation and understanding of Islamic values. Strategies such as blended learning, gamification of religious materials, and the use of digital da'wah media such as Islamic videos and podcasts have proven effective in creating engaging and meaningful learning experiences. This research can provide alternative models of Islamic education that align with the characteristics of the millennial generation. This research can also serve as a reference for educators, curriculum developers, and Islamic educational institutions to design more innovative and responsive learning strategies in line with contemporary developments. Thus, Islamic education not only remains relevant but also has the potential to become a transformative force in shaping a religious and technologically literate younger generation